2010
DOI: 10.1007/s11248-010-9389-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of human cDNA by phosphoglycerate kinase promoter-puromycin cassette in the mouse transthyretin locus

Abstract: To produce a humanized mouse, it is critical to obtain a correct expression of a human gene/cDNA after insertion into a mouse locus. We previously generated a targeted allele in which the PGK-neo cassette, flanked by lox71 and loxP, was inserted into the first exon of the mouse endogenous transthyretin (Ttr) gene in ES cells. Using these ES cells, we showed that a human transthyretin (TTR) cDNA with the PGK-puro cassette can be efficiently inserted into this locus by Cre-mediated recombination, and that the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Northern Blot, Semiquantitative RT-PCR and Quantitative RT-PCR Analyses Total RNA was isolated from the brain, whole eyes, heart, lung, small intestine, testis, skeletal muscle, liver, and kidney. Northern blot and semiquantitative reverse transcriptionpolymerase chain reaction (RT-PCR) analyses were performed according to the methods described by Zhao et al 20 and Li et al, 23 respectively. The nucleotide sequence identity between the mouse and human Rbp4-coding regions is 87%.…”
Section: Generation Of Rbp4orf Knock-in Micementioning
confidence: 99%
“…Northern Blot, Semiquantitative RT-PCR and Quantitative RT-PCR Analyses Total RNA was isolated from the brain, whole eyes, heart, lung, small intestine, testis, skeletal muscle, liver, and kidney. Northern blot and semiquantitative reverse transcriptionpolymerase chain reaction (RT-PCR) analyses were performed according to the methods described by Zhao et al 20 and Li et al, 23 respectively. The nucleotide sequence identity between the mouse and human Rbp4-coding regions is 87%.…”
Section: Generation Of Rbp4orf Knock-in Micementioning
confidence: 99%
“…Northern Blot, Semiquantitative RT-PCR, and qRT-PCR Analyses Northern blot and semiquantitative reverse transcriptionpolymerase chain reaction (RT-PCR) analyses were carried out as described by Zhao et al 16 and Li et al, 19 respectively. The nucleotide sequence identity between the mouse and human Rbp4 coding regions is~87%.…”
Section: Southern Blot Analyses For Isolation Of Targeted Es Cell Clonesmentioning
confidence: 99%
“…The Neo in pEGFP-N1 was driven by its own promoter (SV-40), whereas the Neo in pEGFP-IRES-Neo was driven by the constitutive promoter (human elongation factor, EF) of EGFP separated by an upstream internal ribosome entry site (IRES) sequence. It had been reported that IRES-dependent second gene expression is significantly lower than cap-dependent first gene expression 38 , 39 . The lower expression of Neo may result in less bystander effects and non-transgenic cells will be killed by G418 in shorter time.…”
Section: Discussionmentioning
confidence: 98%